Cellulose biomodification with cutinase fusion proteins - Matamá, Maria Teresa Gonçalves Macedo (2014)
The textile industry presents well succeed examples of enzyme applications on the processing of natural fi bres. The design of hybrid enzymes mimics the strategies that Nature uses to evolve and it is a powerful tool in biotechnology. The production and application of the cutinase fused to carbohydrate - binding modules (CBMs) has provided strong evidences of bei ng an interesting strategy to pursuit. The CBMs act synergistically with the catalytic domains by increasing the effective enzyme concentration at the substrate surface and, for some CBMs, by physical disruption of the solid substrate. Future work is neede d to improve the recombinant production of modular cutinases and to study in detail their affinities toward the cellulose substrates.